Eficácia dos exercícios de alongamento e de estabilização lombar no tratamentro de lombalgia crônica - Maria Angelica Ferreira Leal Puppin (2010)
Low back pain affects over 70% of the population, mostly economically active adults. In addition to the high incidence, chronicity and disability makes this disorder a public health problem in industrialized countries. Kinesitherapy is the first line of choice in physical therapy, but there is no evidence of which type of exercise is more effective. The aim of this study, was to assess, the effectiveness of the GDS method on pain, functional disability, global flexibility and ability to contract the transverse muscle of abdomen (TrA) in individuals with chronic low back pain. 82 patients were randomized into three groups: Stretching (n = 30, age 37.5 ± 12.1) subjected to stretching exercises; Stabilization (n = 27, age 39.0 ± 12) which performed exercises to recruit the deep muscles of the lower trunk and Control (n = 25, age 37.8 ± 13.6) that were not treated. The intervention groups were treated with two weekly sessions lasting 40 minutes, for eight weeks. Pain was assessed by visual analogue scale; functional disability by the Oswestry Index, global flexibility by the third finger to the ground and the ability of TrA contraction by the pressure biofeedback unit. The variables were analyzed before, after and after eight weeks of treatment. We used the single-factor ANOVA with repeated measures and post hoc Holm-Sidak for parametric variables and Friedman's test and Tukey for non parametric at comparisons within and between groups. A significance level of 5% was employed. We also evaluated the relative clinical gain. The results showed significant improvement in pain, functional disability and overall flexibility after treatment and after eight weeks (p <0.05) in the intervention groups. Only the stabilization group was effective in improving the capacity of contraction of TrA (p <0.05). When comparing groups, the two forms of intervention were effective in reducing pain and functional disability (p <0.05). Nevertheless only the Stretching group showed significant improvement in global flexibility (p = 0.01) There was no differences between groups after eight weeks of treatment in functional disability (p = 0.10) and global flexibility (p = 0.07). There was no difference between groups in the ability of contraction of TrA in any of the times evaluated. The two experimental groups had gains on clinical relevance, especially the Stabilization group, except for global flexibility variable in which the stretching exercises had higher gains. The two treatments, stretching and lumbar stabilization used in GDS were effective in reducing pain, functional disability and improving global flexibility, but only the stabilization exercises showed improved ability of the contraction of the TrA in patients with chronic low back pain.